IMPROVING ELEMENTARY STUDENTS’ GREETING VOCABULARY MASTERY THROUGH ENGLISH SONGS : ACTION RESEARCH AT SD MUHAMMADIYAH METRO - Nurul Fitriani; Mai Zuniati; Wiwied Pratiwi (Universitas Muhammadiyah Metro, 2026)
In the digital era, excessive technology use often triggers media saturation, which ultimately makes it difficult for students to focus when learning vocabulary through conventional methods. This research was conducted to improve the vocabulary mastery as a fundamental communication skill for children. The main focus of this study lies in greetings as a basic communicative competence for young learners. The primary objective is to evaluate the effectiveness of English songs in boosting both student engagement and memory retention. By applying a Classroom Action Research (CAR) design following the Kemmis and McTaggart spiral model, this study was conducted over two cycles. This research involved 33 participants consisting of 16 males and 17 females during the 2025/2026 academic year. Data were collected comprehensively through validated researcher-made vocabulary tests, observation sheets, field notes, and visual questionnaires to ensure the validity of the findings. Data analysis was conducted by combining descriptive statistics for quantitative results and qualitative descriptive analysis to capture student behavior patterns. The results showed that the integration of combining English songs and movement significantly improved student engagement and memory, with 90% of students successfully achieving a minimum mastery score of 80 or higher. This figure exceeded the research’s success indicator of 85%. In conclusion, English songs proved to be effective as reliable cognitive and affective tools for restoring students focus amidst a tech-saturated learning environment in early childhood English education. The implications of this research suggest that elementary school educators should integrate musical elements and combined with movement to create a more interactive and enjoyable learning environment.